Pengaruh Makanan terhadap Melanisme Bulu pada Bagian Perut Burung Bondol Jawa (Lonchura Leucogastroides) - Rema Marninda Zahara (MANILKARA: Journal of Bioscience, 2023)
In the wild the Javanese bondol bird (Lonchura leucogastroides) is known as a pest for farmers because it often eats rice grains and seeds that are growing in the fields. If the bondol bird is kept in the wild until it becomes tame, it is predicted that changes in the type of food consumed will affect the color of the hairs that grow on its body parts. The aim of this study was to observe and describe the color changes that occur in the feathers of bondol birds due to the type of food consumed in the form of millet. The research method was carried out in a descriptive qualitative manner. The results showed that giving millet as food for Javanese bondol birds had an impact on the occurrence of changes in the color of the feathers (melanism) on the stomach to black-brown. In fact, generally in the stomach is white.